Target-dependent biogenesis of cognate microRNAs in human cells - Mainak Bose (Nature Portfolio, 2016)
MicroRNAs are a widespread regulatory mechanism and are themselves extensively regulated. Here the authors show regulated miRNA biogenesis by the target mRNA, a layer of regulation that modulates miRNA levels dependent on target availability.